Otimização do processo de sinterização e caracterização termomecânica de uma nova bauxita refratária - Noronha, Luiz Gustavo Moreira (Universidade Federal de São Carlos, 2024)
The global market for refractory grade bauxite (RGB) has historically been supplied by only two distinct sources of ore. This scenario is primarily attributed to the stringent requirements of chemical and mineralogical specifications essential for this particular type of material. The primary suppliers are concentrated in China and Guiana, producing materials with high levels of Al2O3, reduced levels of Fe2O3, and a slight increase in TiO2 content. Upon examining the mineralogical phases of refractory grade bauxite (RGB), it is evident that major producers exhibit higher concentrations of conríndom, tialite, and mullite. Due to these rigorous specifications and the inherent complexity in the production process, no new supplier has emerged as a viable source of RGB thus far. However, a new bauxite mine in Brazil, located in the state of Goiás, at Barro Alto, has demonstrated the capability to produce bauxite with higher Al2O3 content and reduced TiO2 content, thereby differing from global standards in chemical and mineralogical composition, notably by the lower presence of TiO2 in its product. In this context, the present study focuses on the processing of Brazilian refractory grade bauxite, centering on two main areas: i) Optimizing the sintering process of bauxite for the development of benchmark properties; ii) Directly comparing Brazilian bauxite with global standards (refractory grade bauxite from Guiana and China), particularly concerning thermomechanical properties. The data obtained regarding load-bearing refractoriness, along with the results of chemical and mineralogical characterization, have demonstrated that refractory grade bauxite (RGB) derived from Brazilian Bauxite exhibits comparable performance to conventional bauxite products originating from China and Guiana. This finding establishes its viability as a robust alternative to materials traditionally employed globally.
Optimization of the sintering process and thermomechanical characterization of a new refractory bauxite
Keywords: Bauxita refratária; Sinterização; Propriedades termomecânicas; Aplicações em altas temperaturas; Coríndon; Formação de mulita; Teor de Al2O3; Influência do Fe2O3; Separação magnética; Refratariedade sob carga (RUL); Bauxita brasileira; Barro Alto; Goiás; Módulo de ruptura a quente (MRQ); Módulo elástico a quente; Refractory bauxite; Sintering; Thermo-mechanical properties; High-temperature applications; Corundum; Mullite formation; Al2O3 content; Fe2O3 influence; Magnetic separation; Refractoriness under load (RUL); Brazilian bauxite; Hot modulus of rupture (HMoR); Hot elastic modulus; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS